Ecology of coastal waters - Mann, K. H. (University of California Press, 1982)
The approach used in this book differs from that used in many others, in concentrating first and foremost on ecological processes rather than on organisms or populations. In fact, when experimenting with earlier versions, i wondered whether it would be possible to make a useful contribution without naming a plant or an animal.